2014
DOI: 10.1073/pnas.1401674111
|View full text |Cite
|
Sign up to set email alerts
|

Pivotal role of RNA-binding E3 ubiquitin ligase MEX3C in RIG-I–mediated antiviral innate immunity

Abstract: The RIG-I-like receptors, retinoic acid inducible gene-1 (RIG-I), melanoma differentiation-associated protein 5, and laboratory of genetics and physiology-2, are cytoplasmic sensors for RNA viruses that mediate the antiviral innate immune responses. We demonstrate that really interesting new gene-finger domain-and K homology domain-containing MEX3C regulates RIG-I function. MEX3C colocalizes with RIG-I in the stress granules of virally infected cells, and its overexpression causes the lysine-63-linked ubiquiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
140
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(143 citation statements)
references
References 30 publications
2
140
0
1
Order By: Relevance
“…Recent studies have also revealed that the CARD domains of RIG-I, opened after RNA-binding, undergo several posttranslational modifications, which is important for downstream RIG-I signaling, mainly its docking to MAVS. These modifications include: ubiquitination by TRIM25 and the RNA-binding MEXC3 E3 ligases [70,71,72,73,74], phosphorylation by protein kinase C and casein kinase 2, and dephosphorylation by protein phosphatase 1 [75,76,77,78]. Regulation of any of these modifications by specific viruses, cell types or culture conditions may abrogate functional RIG-I signaling downstream of RNA binding, which will make the RNA appear ineffective as a RIG-I ligand, perhaps explaining some of the observed variance and diversity.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have also revealed that the CARD domains of RIG-I, opened after RNA-binding, undergo several posttranslational modifications, which is important for downstream RIG-I signaling, mainly its docking to MAVS. These modifications include: ubiquitination by TRIM25 and the RNA-binding MEXC3 E3 ligases [70,71,72,73,74], phosphorylation by protein kinase C and casein kinase 2, and dephosphorylation by protein phosphatase 1 [75,76,77,78]. Regulation of any of these modifications by specific viruses, cell types or culture conditions may abrogate functional RIG-I signaling downstream of RNA binding, which will make the RNA appear ineffective as a RIG-I ligand, perhaps explaining some of the observed variance and diversity.…”
Section: Resultsmentioning
confidence: 99%
“…Riplet has been shown to mediate the K63-linked polyubiquitination of the C-terminal region of RIG-I. In addition, TRIM25 and MEX3C have both been shown to mediate the K63-linked ubiquitination of RIG-I CARDs at lysine 172, 99, or 169, respectively (10,(16)(17)(18)(19). Different E3 ubiquitin protein ligases mediate different ubiquitination sites of RIG-I, indicating that the coordinated regulation of these molecules is required for the RIG-I-mediated antiviral immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…E3 ubiquitin ligases have been reported to be involved in the regulation of RIG-I signaling (14,15). For example, E3 ubiquitin ligases TRIM25, Riplet, and MEX3C can mediate K63-linked polyubiquitination of human RIG-I (10,(16)(17)(18)(19), thus positively regulating RIG-I-mediated signaling. On the contrary, RING finger protein (RNF) 125 (RNF125) or c-Casitas B lineage lymphoma (c-Cbl) catalyzes K48-linked ubiquitination and promotes proteasomal degradation of RIG-I, thus negatively regulating RIG-I-mediated signaling (20,21).…”
mentioning
confidence: 99%
“…The cells were lysed in 20 mM Tris-HCl, pH 8.0, 150 mM NaCl, 1 mM EDTA, 0.5% Nonidet P-40, and the cell lysates were immunoprecipitated with 5 l of anti-Myc antibody-conjugated agarose beads (c-Myc 9E10, sc-40 AC, Santa Cruz Biotechnology). The samples were applied to SDS-PAGE and then immunoblotted as described previously (8). The used antibodies were listed as below: anti-Myc rabbit antibody (ϫ1000 dilution, Sigma); anti-FLAG rabbit antibody (ϫ1000 dilution, Sigma), or anti-␤-actin goat antibody (ϫ1000 dilution, I-19, Santa Cruz Biotechnology).…”
Section: Methodsmentioning
confidence: 99%